Performance Analysis of Arbitration Scheduling Algorithm Based on RR Optimization for Network-on-chips. Issue 1 (January 2021) - Ma, Ruofei; Bao, Liyong; Ding, Hongwei; Guan, Zheng
Abstract: The RR arbitration algorithm commonly used in the current Network-on-chips cannot meet the requirements for low power consumption and rapid response under high load conditions, with the continuous development of microelectronics technology. In order to solve this problem, based on the idea of non-competitive transmission and parallel optimization, this paper improves on the RR algorithm to obtain a MAC layer arbitration scheduling algorithm suitable for the Network-on-chips. By optimizing the service and query transfer process in parallel, the algorithm reduces the queue length of information grouping in the system and shortens the query period of the system. The algorithm model is established by using Markov process and probability generating function, mathematically analyze the first-order characteristics of the system, and obtain an accurate solution. The simulation model of the algorithm is established based on the simulation platform to verify the accuracy of the precise solution. After optimization, the system's average queue length and average cycler have been greatly improved.